CIRCULAR ECONOMY TRANSFORMATION IN MSMES: SUSTAINABLE BUSINESS MODEL INNOVATION TO ENHANCE ECONOMIC AND ENVIRONMENTAL PERFORMANCE - Iman Supriadi; Mochamad Fatchurrohman; Etin Puspita Sari (MESP–FEB UNS, 2025)
This study analyzes the transformation of the circular economy in micro, small, and medium enterprises (MSMEs) through sustainable business model innovation and evaluates its impact on economic and environmental performance. The research aims to identify key factors influencing the successful implementation of circular economy principles and propose a theoretical framework relevant to developing countries. Employing a qualitative approach, this study utilizes a case study design and secondary data analysis, drawing from peer-reviewed journals, industry reports, and policy documents. Thematic analysis is applied to extract key patterns and relationships that support circular economy adoption in MSMEs. The findings reveal that integrating resource efficiency, waste reduction, and digital technologies enhances MSME competitiveness while promoting sustainability. Key success factors include leadership commitment, strategic partnerships, and access to technology and financing. This study contributes to the literature by offering a comprehensive framework that integrates circular economy principles with business model innovation in the MSME context. Practically, it provides strategic insights for policymakers, business leaders, and academics to accelerate the transition toward sustainable business models. Future research should focus on empirical validation and sector-specific applications to strengthen the framework’s applicability. By adopting circular economy strategies, MSMEs can enhance their resilience, drive sustainable economic growth, and contribute to global environmental goals.